Analysis Of the Implementation of Transparency, Accountability, and Internal Control Principles in Financial Management - Betha Ursula Siallagan; Nanu Hasanuh (Jurnal Ekuilnomi, 2026)
This study aims to analyze the implementation of the principles of transparency, accountability, and internal control in financial management through qualitative methods with a literature review approach. Data were collected from various scientific literature, regulations, and related audit reports to explore the gap between governance theory and practice in the field. The analysis results show that although organizations have attempted to meet reporting standards administratively, implementation often gets bogged down in bureaucratic formalities that neglect substantive aspects. Transparency is still hampered by data accessibility, while accountability tends to focus on legal compliance rather than value. The study concludes that strengthening internal control systems and ethical commitment from leaders are key to transforming organizational culture toward financial governance that is truly integrity and credible